PERAN RELAWAN PAJAK DALAM MELAYANI WAJIB PAJAK DI KPP PRATAMA JAKARTA TAMANSARI - Melvina; Widjaja, Djeni Indrajati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Tax Volunteers is one of the Merdeka Campus programs which provides students with the opportunity to develop social awareness and sensitivity. One of the Rajak Volunteer activities was carried out at KPP Pratama Jakarta Tamansari from February to April 2023. This activity was carried out to help the public to be more compliant in fulfilling their tax obligations in Indonesia. Various activities were carried out during implementation, including: activating the Electronic Filing Identification Number (EFIN), procedures for reporting Annual Tax Reports electronically, and verifying the Population Identification Number to become a Taxpayer Identification Number. The main aim of this activity is to help Taxpayers in Tamansari District to easily resolve various tax problems using education and consultation methods. This method is carried out by providing tax information such as activation, reporting and verification online via the Directorate General of Taxes website. The results of this activity can be said to be positive, seen from the Taxpayer being able to absorb the information provided and put it into practice independently. The implementation of this activity has provided benefits for many stakeholders, including Taxpayers being able to solve their problems, tax officers getting easier work, and Tax Volunteers having the opportunity to contribute to society.